Mentoring in Maggot Cultivation as Cheap Catfish Feed, at the Karang Taruna Padukuhan Bulu, Semanu, Gunungkidul, Yogyakarta - Yunianta Yunianta; Putriana Kristanti; Citravia Agustin (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
Karang Taruna in Padukuhan Bulu, Semanu, Gunungkidul Regency, Special Region of Yogyakarta, has been cultivating catfish since 2018. The problem is that the cost of feed was getting higher so farmers' income was getting lower. This community service aims to introduce and provide mentoring for maggot cultivation for cheap catfish feed so that it can bring benefit to the catfish farming business. From observation and problem identification by the community service team, a program was arranged to produce cheap feed with maggot ingredients, so that the catfish farm can operate more economically and the farmers' incomes can be increased. The activity was carried out for four months, starting from the preparation of making maggot lair cages, maintaining maggot from eggs, and using it as maggot cages. The target is to provide cheaper catfish feed as a substitute for factory-made commercial feed. The results obtained were that Karang Taruna members managed to get catfish feed made from maggots, at a cheaper cost. Besides that, the level of catfish production increased (an increase in income of Rp. 366,000 per pond per period). Hopefully, this activity can be followed up by the local government and the welfare of the younger generation can be improved on an ongoing basis.